Characteristic of Variable Compression Ratio Diesel Engine Operating on Diesel and Biodiesel B20. Issue 1 (June 2020) - Amaliyah, N; Mire, B; Putra, A E E; Syam, M; Zakariah, H
Abstract: The limitation of natural resources especially crude oil employed in automotive engine has made an attention to switch over to biodiesel. Biodiesel is known as carbon neutral and produce no carbon dioxide leads to decrease of pollution and potentially improve the engine performance. In this study, an experimental investigation on variable compression ratio diesel engine is observed based on the engine performance using the VCR Engine test setup 1 cylinder, 4 strokes with EGR (computerized). The effect of compression ratio change on the torque, specific fuel consumption (SFC), indicated power, and brake thermal efficiency has been studied using mineral diesel and biodiesel B20. When increasing the compression ratio from 13 to 18, it was found that torque was significantly increased when using biodiesel B20. As the torque increase resulted in higher indicated power. The decreasing of SFC were about 44% and 11% for mineral diesel and biodiesel B20 respectively. Specific fuel consumption was optimum at 0.21 g/kW.h at a compression ratio of 16 using mineral diesel.